Ecological risk assessment of heavy metals in soil, water and river sediments in and around the Bued River - Bautista, Camilla C.; Quiocho, Rose E.; Diola, Ma. Brida Lea D.; Resurreccion, Augustus C. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Heavy metals in the environment may cause harmful effects not only to humans but also to ecological receptors. Previous studies showed that elevated concentrations of heavy metals, specifically lead and arsenic were present in residential soils, surface water and river sediments in and around the Bued River. This study aims to quantitatively measure risk to ecological receptors due to possible exposure to heavy metals. Baseline information about heavy metal concentrations were aggregated and processed. Vegetation and soil samples were also collected from five established sampling points. Results of the analysis show that arsenic in soil ranges from 3.22-50.72 mg/kg while 50.68-641.21 mg/kg for lead. Despite the relatively higher lead concentration on soils, lead in all of the collected vegetation samples were below detection limit. Average bioconcentration of arsenic and lead to plant is 0.085474 and 0.001472, respectively. Chronic and Acute Hazard Quotients and Hazard Indexes of media receptors algae, earthworm and fish were calculated with exposure set to media concentration of their dwelling. Similarly, mentioned parameters are also calculated for terrestrial receptors, while their dosage is a function of oral ingestion and dermal contact. Maximum allowable complementary pairs of media concentration and reference dosage are calculated and showed large margin for incremental increase of heavy metal in case of sediment tank spills and the like. Based on the Hazard Quotient and Hazard Indexes, It was found that media receptors will likely to have Moderate Impact affecting sensitive and standard species whereas terrestrial receptors will probably to experience Negligible Impact concerning only sensitive species. The SADA software was also used to spatially model ecological risk and heavy metal exposures.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Soils -- Heavy metal content; Plants -- Effect of heavy metals on